CORAK KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGEMBANGKAN PENDIDIKAN ISLAM - Fauzi, Ahmad (LPPI Universitas Al-Qolam Malang, 2018)
The style of the principal's leadership in developing educational institutions has three models: the authoritarian type (autocratic style of leadership), the type of laissez faire (laissez faire style of leadership), and the democratic type (democratic style of leadership). The most ideal type is the third one. The three models are seen in the principal's task which includes two domains, namely the administrative domain and the supervision shutter. In the administrative area, the task of the principal is related to the activities of providing, regulating, maintaining, completing material facilities and personnel of the school. Whereas as a supervisor, the principal is tasked with providing guidance on supervision and assessment of problems related to technical management and the development of education and teaching to create a better situation and education. Keywords: principal, leadership, models.